Cohen’s criteria for interpreting practical significance indicators: A critical study - AlWahaibi, Ibrahim Said Humaid; Al-Hidabi, Dawood Abdulmalek Yahya; AlKharusi, Hussain Ali Talib (SciencePark Science, Organization and Counseling (SPROC), 2020)
The present study aimed at clarifying the various shortcomings of the Cohen’s criteria for the interpretation of the values of the practical significance indicators. The hypothetical data were used for two experimental and control groups and calculating the paired-samples t-test. To clarify the inadequacy of Cohen’s criteria in interpreting practical significance indicators, it was compared with another criterion which is Black’s Modified Gain Ratio. Through the compatibility of mathematical equations to calculate the practical significance and the values of the interpretations of the correlation coefficient, the present study suggested that a criterion for the practical significance should be as follows: small when the values of the index (d) are less than (0.631), medium when the values are between 0.631 and 1.50 and large when the values are equal to or greater than (1.51). The study showed the justifications that distinguish this criterion from the Cohen criterion.